Construction firm’s efficiency in Malaysia - Zahariah Sahudin; Wan Mansor Wan Mahmood; Zaidi Isa; Aminah Shari (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2015)
Construction firms in Malaysia have seen a strong growth. It has indicated being a potential as contributor to the nation’s GDP. Records have also indicated that Shariah compliant organization have sustained resilience in various economic challenges. Therefore, this paper examines the technical efficiency of Shariah-compliant construction firms in Malaysia for the year between 2002 through 2011. Using Stochastic Frontier Approach (SFA) with one output (profit) and four inputs (labour costs, physical capital, financial capital and current asset) the results indicated that average technical efficiency is 55.59%, an indication of input waste of 44.41%, in terms of labour, financial capital, physical capital and current assets in producing an output. The mean efficiency achieved implies that the Shariah-construction industry is far from realizing 100% of its potential output. The findings are relevant to the ongoing debate on the issue of inefficiency of Shariah-compliant firm in realizing optimal output. The results suggest that in emerging economies like Malaysia, full efficiency will generate industrial growth which in turn will contribute to the nation economic growth.